A system dynamics prospective analysis of extended producer responsibility policies: a business for a few (2025)
This paper presents a prospective analysis of the evolution of the Extended Producer Responsibility (EPR) system for waste management in developing countries, using the case of Colombia’s packaging sector. The system dynamics model highlights two distinct phases in the evolution of the EPR system: before and after achieving maximum collection and certification targets. In the pre-target phase, the simulation shows a boom in the creation of producer organizations (PROs), collectors, and transformers, driven by increasing demand. This growth is influenced by the magnitude of collection goals, stepwise increases, and the level of vertical integration between PROs and collectors, which enhances profitability. However, entry barriers and the inability of some firms to cover regional waste collection eventually slow this boom. In the post-target phase, the market experiences firm exits and cost reductions, reaching an equilibrium. This trend is further accelerated if producers reduce waste, leading to market concentration, especially among transformers. The analysis suggests that continuous increases in collection and transformation targets are necessary to maintain market competitiveness, avoiding dominance by a few firms. The findings emphasize the importance of local conditions in shaping EPR policy outcomes. The proliferation of PROs in Colombia differs from trends in other countries, illustrating the influence of policy parameters on market behavior. System dynamics prove to be a valuable tool for simulating future scenarios, informing policy design, and understanding the impact of EPR on eco-design, circular economy practices, and regulatory compliance. The study advocates for more robust decision-support tools to enhance EPR policy effectiveness an avoid market concentration and high costs.